6m+5n-3m+11n=

Simple and best practice solution for 6m+5n-3m+11n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6m+5n-3m+11n= equation:


Simplifying
6m + 5n + -3m + 11n = 0

Reorder the terms:
6m + -3m + 5n + 11n = 0

Combine like terms: 6m + -3m = 3m
3m + 5n + 11n = 0

Combine like terms: 5n + 11n = 16n
3m + 16n = 0

Solving
3m + 16n = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-16n' to each side of the equation.
3m + 16n + -16n = 0 + -16n

Combine like terms: 16n + -16n = 0
3m + 0 = 0 + -16n
3m = 0 + -16n
Remove the zero:
3m = -16n

Divide each side by '3'.
m = -5.333333333n

Simplifying
m = -5.333333333n

See similar equations:

| 2p^8+5p^4q-12q^2= | | q+.33=.5 | | (5x^2+4x-8)+(3x^2+3x+14)-(8x^2-11)= | | -14y^2-9y^2+12y^2+61xy^2-18xy^2= | | -28-2.6q=-3.8q+4(4.3q+1) | | (3x^2+2x-3)+(5x^2+4x+13)-(8x^2-18)= | | -.7q-(-4+0.9q)=2.8 | | 3.2-9x+7.1-3x=0 | | 7x-1-(x-1)=5x-7 | | (4x+7)-(-2x^2-5x+7)= | | (9x-5)*(9x-5)= | | 7a^3-3a^2+4a+9= | | (-6x+5)+(-4x^2+6x+3)= | | (x-2-3i)(x-2+3i)(x+1)(x-2)=0 | | 2x^225= | | whyunot=work | | 40=110-30t | | 8x+2h=19 | | dropthe=base | | d=110-30t | | this=stupid | | this=dumb | | 3y+2x=-11 | | you=dumb | | 6n^2+24n-18= | | ln=e | | 3*3+34=4 | | n^3+12n^2-23n-10=0 | | 2x+7=6x+49 | | 50x^2=50 | | Y+e=93 | | e(x)-4e(-x)=-3 |

Equations solver categories